Rap2b, a novel p53 target, regulates p53-mediated pro-survival function - Zhang, Xinyue (Landes Bioscience, 2013)
The tumor suppressor p53 is a critical regulator of apoptosis and cell cycle arrest/pro-survival. Upon DNA damage, p53 evokes both cell cycle arrest/pro-survival and apoptosis transcriptional programs. The ultimate cellular outcome depends on the balance of these two programs. However, the p53 downstream targets that mediate this cell fate decision remain to be identified. Using an integrative genomic approach, we identify Rap2b as a conserved p53-activated gene that counters p53-mediated apoptosis after DNA damage. Upon DNA damage, p53 directly binds to the promoter of Rap2b and activates its transcription. The reduction of Rap2b levels by small interference RNA sensitizes cells to DNA damage-induced apoptosis in a p53-dependent manner. Consistent with its pro-survival function, analysis of cancer genomic data reveals that Rap2b is overexpressed in many types of tumors. Anchorage-independent growth assays show that Rap2b has only weak transformation activity, suggesting that it is not an oncogene by itself. Together, our results identify Rap2b as a new player in the pro-survival program conducted by p53 and raise the possibility that targeting Rap2b could sensitize tumor cells to apoptosis in response to DNA damage.